Rare types of breast carcinoma - STEPONAVIČIENĖ, Laura; GUDAVIČIENĖ, Daiva; MEŠKAUSKAS, Raimundas (Acta medica Lituanica, 2012)
Background. Breast cancer is a heterogeneous disease that encompasses several distinct entities with remarkably different characteristics. One of very important cancer characteristics is its histological type.Materials and methods. We used Pubmed and Medscape databases and analyzed original articles and literature reviews about rare histological types of breast cancer.Results and discussion. World Health Organization (WHO) presents a detailed classification of breast cancers. According to this classification, cancers are divided into epithelial, mesenchymal, fibroepithelial tumors. Malignant lymphoma, metastatic tumors can also be found in the breast. WHO also marks tumors of the nipple, male breast cancer and myoepithelial lesions. In this paper, only the invasive epithelial tumors are discussed. Most tumors are derived from mammary ductal epithelium, and up to 75% of the breast cancers are ductal carcinomas. The second most common epithelial tumor type is invasive lobular carcinoma which comprises 5–15% of the group. There are more than a dozen variants which are less common. They comprise less than 10% of breast tumors. Their clinical behavior can differ greatly. So, it is important to know their main characteristics in order to make the best treatment choice and to foresee prognosis. We shortly describe the epidemiology, diagnostics, clinical and immunophenotypic features, prognosis and predictive factors of rare epithelial breast tumors.